Menumbuhkan Literasi Digital pada Ibu Rumah Tangga Di Lingkungan Distapang Kabupaten Kebumen - Ika Neni Kristanti (Jurnal Inovasi Pengabdian Masyarakat, 2024)
Digital literacy for housewives has an important role in finding accurate and reliable information. In the current era of information flooding, housewives need to have the ability to sort out accurate and reliable information, especially regarding health, children's education and family finances, Mother households need to understand how to use the internet and social media safely, and protect themselves from online fraud and cyberbullying. The method for implementing this community service activity is using the experiential learning method. The aim of this community service activity is so that housewives are expected to be able to access useful information and services to improve the quality of family life, especially in managing household finances. Housewives can also learn and develop their own potential through various digital platforms. The conclusion of this community service activity is that increasing digital literacy among housewives is not only about acquiring technological skills, but also about empowering them to take an active role in the digital era, especially regarding financial management. With the right support and access to relevant resources, stay-at-home moms can overcome challenges and expand their digital skills regarding financial management, bringing lasting benefits to themselves and their families